Productivity, nutrient harvest index, nutrient balance sheet and economics of lowland rice (Oryza sativa) as influenced by composts made from locally available plant biomass - DAS, ANUP; BAISWAR, P; PATEL, D P; MUNDA, G C; GHOSH, P K; CHANDRA, S (The Indian Journal of Agricultural Sciences, 2010)
A field study was conducted during 2004–06 on the performance of 8 different type of composts prepared from rice (Oryza sativa L.) straw, Eupatorium adenophorum Spreng, Lantana camara L. and weed mixtures were evaluated (10 tonnes/ha) and compared with the recommended NPK (80:60:40 kg/ha) and farmyard manure (10tonnes/ha) on productivity, nutrient harvest index and nutrient balance sheet of lowland rice. Two composting procedures were tried, one was microbial enriched compost consisting of biomass + cowdung (1:1 on weight basis) + compost culture with cowdung slurry and another was microbial and nutrient fortified compost consisting of microbial enriched compost + rock phosphate @ 2.5% (w/w) + neem cake 1%. Bioinoculums such as cellulose decomposers (Aspergillus terrus, Trichoderma harzianum, T. viride, T.virens), P-solubilizing microbes (Bacillus polymyxa and Pseudomonas striata) and free-living N-fixers (Azotobacter spp) were used as compost culture to hasten the composting process and improve the quality of the composts. The results indicated that significantly (P < 0.05) higher grain yield was recorded with rice straw microbial and nutrient fortified compost followed by the Eupatorium microbial and nutrient fortified compost, which were 5.5 & 46 % and 2 & 38 % higher than recommended NPK and control, respectively. The nutrient uptake and soil fertility status was found to be significantly improved due to application of various composts. Rice straw microbial and nutrient fortified compost recorded the highest net returns (Rs 29 420/ha), followed by Eupatorium microbial and nutrient fortified compost (Rs 28 530/ha).